Physics competitions in the time of a pandemic: 3D printing as a new approach to the quantitative investigation of Cartesian divers at home - Bley, Jonas; Pietz, Antony; Fösel, Angela; Schmiedeberg, Michael; Heusler, Stefan; Pusch, Alexander (European Journal of Physics, 2021)
Despite the difficult circumstances due to the COVID-19 pandemics, physics students can tackle interesting questions that are part of physics competitions as the German Physicists' Tournament (GPT) 2020. Due to the COVID-19 pandemics in 2020, many competitions such as the GPT are held online. Furthermore, the usual options of equipment offered by the supervising university institutions could not be used by the students. The problems of the GPT 2020 therefore had to be chosen in such a way that they could be examined at home using simple means. One of these supposedly simple but profound experiments—the Cartesian diver—is described in this article. The physics of the Cartesian diver has been discussed before Fakhruddin (2003 Phys. Teach. 41 53), Güémez et al (2002 Am. J. Phys. 70 710) and De Luca and Ganci (2011 Phys. Educ. 46 528), as well as various modifications (Ivanov and Nikolov 2019 Phys. Educ. 55 025006). We present a new way of investigating Cartesian divers quantitatively by using 3D printing and common household materials. The paper is addressed to undergraduate students and educators teaching physics at university.<br